The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.rser.2009.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The potential of solar-driven humidification–dehumidification desalination for small-scale decentralized water production

Abstract: World-wide water scarcity, especially in the developing world, indicates a pressing need to develop inexpensive, decentralized small-scale desalination technologies which use renewable resources of energy. This paper provides a comprehensive review of the stateof-the-art in one of the most promising of these technologies, solar-driven humidification-dehumidification (HDH) desalination. Previous studies have investigated many different variations on the HDH cycle. In this paper, performance parameters which ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
132
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 358 publications
(159 citation statements)
references
References 64 publications
0
132
0
1
Order By: Relevance
“…A water heater between the humidifier and dehumidifier provides the heat input to the system. This particular embodiment of HDH is known as a closed air, open water (CAOW) cycle; there are several others that have been studied in detail [1,7], but will not be discussed further here.…”
Section: Humidification-dehumidification Desalinationmentioning
confidence: 99%
“…A water heater between the humidifier and dehumidifier provides the heat input to the system. This particular embodiment of HDH is known as a closed air, open water (CAOW) cycle; there are several others that have been studied in detail [1,7], but will not be discussed further here.…”
Section: Humidification-dehumidification Desalinationmentioning
confidence: 99%
“…From the literature cited above and a previous literature review [1], we have found no study which systematically attempts to improve and/or optimize the cycle performance by modifying the cycle itself. Hence, the objective of this paper is to analyze the thermodynamic performance of various HDH cycles in literature and to propose novel high-performance variations on those cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Solar thermal technologies, i.e., the conversion of the sunlight to thermal energy, are being developed for many applications such as power generation, domestic water heating, desalination, and other industrial processes. [1][2][3][4][5][6][7] Steam and vapor generation is often desired in these applications, but the dilute solar flux (1000 W/m 2 ) does not provide enough power per unit area of the absorber to reach the required high temperatures and to compensate for the large latent heat of water vaporization. Optical…”
mentioning
confidence: 99%